Key Stone Entity in Paediatric Dentistry: Tell Play Do - Sabari Lavanya, PonnuduraiArangannal, Jeevarathan J, Amudha S, AarthiJ, Vijayakumar M (Indian Journal of Forensic Medicine & Toxicology, 2020)
The child behaviourmanagement in paediatric clinic is the way by which the dental health care team effectivelyand efficiently performs treatment for a child. To provide dental care for children good communicationskills are necessary.Dental fear is a common, essential, and inevitable emotion that appears as a responseto the stressful situation, which raises children’s anxiety level, resulting in reduced demand for paediatricdental care. Behaviour management is widely agreed to be a key factor supplying dental care for children.TSD technique was modified into Tell?Play?Do (TPD) technique, using the concept of learning by doing inreducing children’s fear and anxiety to dental treatment and promoting adaptive behaviour.